Macrophages: The Good, the Bad, and the Gluttony - Ross, Ewan A.; Devitt, Andrew; Johnson, Jill R. (Frontiers in Immunology, 2021)
Macrophages are dynamic cells that play critical roles in the induction and resolution of sterile inflammation. In this review, we will compile and interpret recent findings on the plasticity of macrophages and how these cells contribute to the development of non-infectious inflammatory diseases, with a particular focus on allergic and autoimmune disorders and the ability of macrophages to clear apoptotic immune cells. Rheumatoid arthritis (RA) is a chronic autoimmune-driven spectrum of diseases where persistent inflammation results in synovial hyperplasia and excessive immune cell accumulation, leading to remodeling and reduced function in affected joints. Macrophages are central to the pathophysiology of RA, driving episodic cycles of chronic inflammation and tissue destruction. Modulation of macrophage phenotype and function remains a key therapeutic goal for the treatment of this disease. Allergic asthma is associated with Th2-polarised airway inflammation, structural remodeling of the large airways, and airway hyperresponsiveness. Macrophage polarization has a profound impact on asthma pathogenesis, as the response to allergen exposure is regulated by an intricate interplay between local immune factors including cytokines, chemokines and danger signals from neighboring cells. Targeting regulators of macrophage plasticity is currently being pursued in the treatment of allergic asthma and other allergic diseases. Macrophages promote the re-balancing of pro-inflammatory responses towards pro-resolution responses and are thus central to the success of an inflammatory response. It has long been established that apoptosis supports monocyte and macrophage recruitment to sites of inflammation, facilitating subsequent corpse clearance. This drives resolution responses and mediates a phenotypic switch in the polarity of macrophages. The impact of such interactions may result in repair or disease in different contexts. In this review, we will discuss the origin, characterization, and activity of macrophages in sterile inflammatory diseases and the underlying mechanisms of macrophage polarization and apoptotic cell clearance, in order to provide new insights into therapeutic strategies that could exploit the capabilities of these agile and responsive cells.